KERJASAMA GURU BIMBINGAN KONSELING DENGAN GURU MATA PELAJARAN IPS DALAM MEMBANTU KEGIATAN BELAJAR SISWA - Sawal Mahaly (FKIP UMN ALWASHLIYAH, 2021)
Effective guidance and counseling services cannot be carried out properly without the cooperation between BK teachers and related parties both inside and outside the school. cooperation with parties within the school, among others, with subject teachers. In carrying out counseling guidance activities, especially social studies subject teachers are expected to be able to assist BK teachers in collecting various information about student needs and student problems both in learning activities and outside learning activities, so that these students can be helped to overcome the problems they are experiencing. The purpose of this study is to find out how the cooperation between BK teachers and social studies subject teachers in assisting student learning activities. This type of research is descriptive research. The results of the study illustrate that the collaboration between BK teachers and social studies subject teachers in assisting students' learning activities at SMA Negeri 44 Central Maluku is low with an average of 56%.